AKSES INFORMASI: TELAAH ATAS MAKNA DAN FUNGSI - Subur, Subur (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2011)
In the stones age, humans who muscular who wins. In the era of farming, people who have large trads of land that lucky. In the industrial era, people who have Capital, the vidorious. But in the current information age, people who have information that would benefit. An information and access to information has become a staple of human life in this era, although sometimes not accompanied by adequate reading craze. But with the rapid development of media/ sources of good information online, print media, television, access to information increasingly easy to obtain. The importantthing is readytosociety with a flood of information.